Evaluasi Sediaan Gel Anti Jerawat Kombinasi Ekstrak Etanol Daun Cabai Rawit dan Ekstrak Etanol Daun Sirsak - Dimas Setiyono; Deden Mulya Prayoga; Herlan Budi Kusuma; Dina Febrina (JURNAL ILMU KEFARMASIAN INDONESIA, 2023)
Acne is a skin disease that usually occurs near adulthood. Acne is caused by several bacteria namely Staphylococcus epidermidis, Propionibacterium acnes, and Staphylococcus aureus. The alternative acne treatment uses cayenne pepper leaves (Capsicum frutescens L.) and soursop leaves (Annona muricata L.). The research aimed to find out the best formulation and activity of the ethanol extract gel of cayenne pepper leaves combined with the ethanol extract of soursop leaves as an inhibitor for acne-causing bacteria. This research is an experimental research type with 3 formulation designs, each of which was made with concentrations of ethanol extract from cayenne pepper leaves and ethanol extract from soursop leaves, namely F1 (1% and 1%), F2 (3% and 3%), and F3 (5 % and 5%), then tested the physical properties, antibacterial test and physical stability test of the preparation then analyzed the data with one-way ANOVA p-value <0.05. The results showed that the gel preparations were stable in terms of organoleptic, homogeneity, spreadability, adhesion, and viscosity, while there was a change in pH after the physical stability test using the cycling test method. The F2 gel preparation had the best bacterial inhibition, namely Staphylococcus aureus of 10.83 mm. Then the F3 gel preparation best inhibited Staphylococcus epidermidis bacteria by 9.56 mm and Propionibacterium acnes by 10.4 mm.